(untitled) (Bangladesh Journal of Botany, 2023)
Pot experiments were carried out to study characteristics of soil selenium (Se) enrichment and its influence on Chinese medicinal plant Abelmoschus manihot, and selenium contents in aboveground parts of A. manihot under conditions of natural Se-rich, low soils and exogenous Se addition were analyzed. Results indicated that contents of total Se and various Se fractions of natural Se-rich soil were significantly higher than that of Se-low soil (P < 0.05), and Se content in aboveground parts of A. manihot grown in natural Serich soil was significantly higher than that in natural Se-low soil (P < 0.05). The Se content in aboveground parts of A. manihot increased with the increase of soil total Se content, soil pH and contents of various Se fractions, showing significant tolerance to high Se. Moreover, it was initially found that A. manihot could effectively absorb soil Se even in relatively low Se soil conditions (soil Se content of 0.11 0.12 mg/kg) and thus reaching the standard of Se-rich crops. Bangladesh J. Bot. 51(4): 961-970, 2022 (December) Special